The Relationship Between Exercise Habits And Sleep Quality In Adults Aged 45-55 Years (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to investigate the relationship between exercise habits and sleep quality in individuals aged 45-55. A descriptive quantitative study with a cross-sectional design was employed. The sample consisted of 40 women aged 45–55 who actively participate in gymnastics in Pasar Terusan Village, RT 09, with data collected via the Pittsburgh Sleep Quality Index (PSQI) and an exercise habit questionnaire. The Chi-Square test revealed a significant relationship between exercise habits and sleep quality, with a significance value (Asymp. Sig. 2-sided) of 0.022 (p < 0.05). These findings suggest that regular exercise is significantly associated with sleep quality in middle-aged adults. However, the relationship may not be linear, indicating that the intensity and timing of exercise are crucial factors that warrant further investigation to provide optimal health recommendations for this demographic.